Pengaruh Servant leadership terhadap Kinerja Pegawai melalui Teamwork sebagai Variabel Intervening pada BRIDA Provinsi Jambi - Bramantyo Abdi Saputra; Zulfina Adriani; Dian Mala Fithriani Aira (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The purpose of this study is to determine the effect of servant leadership on employee performance through teamwork as an intervening variable at BRIDA Jambi Province. This type of research is quantitative research. The population in this study were all employees at BRIDA Jambi Province, totaling 40 people with a research sample of 40 people. Data collection used a questionnaire that had been tested for validity and reliability. The research analysis method used descriptive statistical analysis using the Structural Equation Model (SEM), with Smart PLS 4.0 Software (Partial Least Square) as a tool to process the data. The results of this study indicate that servant leadership has a positive and significant influence on employee performance, servant leadership has a positive and significant influence on teamwork, teamwork has a positive and significant influence on employee performance, servant leadership has a positive and significant influence on employee performance through teamwork as an intervening variable.